Pengukuran Unjuk Kerja MPPT Photovoltaic Stand-Alone Dalam Kondisi Perubahan Bertahap Iradiasi Matahari - Rhezal Agung Ananto; Hanaldi, Wahyu; Harijanto , Priya Surya; Gumilang , Binar Surya; Santoso, Asfari Hariz (Elposys: Jurnal Sistem Kelistrikan, 2025)
Nowadays, renewable energy is an important energy. This study aims to analyze the performance of Maximum Power Point Tracking (MPPT) in Stand-Alone Photovoltaic (PV) systems in dealing with gradual changes in solar irradiation. The main focus of the study is the comparison between irradiaton to MPPT product. The research methodology involves the use of several types and sizes of PV to obtain representative data. Variations in solar irradiation intensity are used to simulate various real conditions. The initial objective is to assess the performance of specially designed MPPT and ensure that the system can function properly in optimizing PV power under changing irradiation conditions. The main objective is to analyze the performance of MPPT in Stand-Alone Photovoltaic systems as a whole, considering variations in PV types and sizes, as well as differences in solar irradiation levels. The results of this study are expected to provide in-depth insight into the effectiveness of MPPT under various operational conditions. Trials were conducted both in the laboratory and in the field to ensure the validity of the results. Thus, this study makes a significant contribution to the development of more reliable and efficient Stand-Alone Photovoltaic technology. The findings of this study are expected to be the basis for improving MPPT design and increasing the performance of Stand-Alone Photovoltaic systems in dealing with environmental variations and different operational conditions.